2023
DOI: 10.3389/fpsyg.2023.1116932
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between perceived teacher support and student engagement among higher vocational students: A moderated mediation model

Abstract: IntroductionStudent engagement is a best predictor variable of student’ development and success. It can be highly influenced by internal and external environmental factors, such as perceived teacher support.MethodsIn order to explore the influence of perceived teacher support on student engagement among higher vocational students, this study conducted a questionnaire on 1,136 Chinese higher vocational students using perceived teacher support, basic psychological needs satisfaction, learning drive, student enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…research demonstrated that students who were emotionally supported by their professors were more likely to be motivated to grasp the material, like learning, succeed academically, and display task-related behaviors. When it comes to their academic performance, students who believe their professors support them do better than those who do not [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…research demonstrated that students who were emotionally supported by their professors were more likely to be motivated to grasp the material, like learning, succeed academically, and display task-related behaviors. When it comes to their academic performance, students who believe their professors support them do better than those who do not [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Teacher support had no direct impact on learning ability satisfaction. The improvement of learning ability was achieved without the support of teachers [97,98]. Therefore, teacher support had an indirect impact by acting on other internal factors.…”
Section: Influence Analysis Of External Factors On the Learning Abili...mentioning
confidence: 99%